Deficiency of the palmitoyl acyltransferase ZDHHC7 modulates depression-like behaviour in female mice after a mild chronic stress paradigm - Christa Hohoff; Nicole Kerkenberg; Mingyue Zhang; Weronika Palkowska; Lydia Wachsmuth; Maja Peng; Lena Stiehl; Christiane Schettler; Johannes C. S. Zang; Andreas Huge; Evgeni Ponimaskin; Cornelius Faber; et al. (Translational Psychiatry)
Abstract Chronic stress (CS) is a debilitating condition that negatively affects body and brain. In mice, CS effects range from changes in behaviour and brain microstructure down to the level of gene expression. These effects are partly mediated by sex and sex steroid hormones, which in turn are affected by the palmitoyl acyltransferase ZDHHC7. ZDHHC7 might modulate also the response to CS via palmitoylation of sex steroid hormone receptors and other proteins critical for neuronal structure and functions. Therefore, we aimed to investigate the role of ZDHHC7 in response to CS on different system levels in a mouse model of Zdhhc7-deficiency. Female and male Zdhhc7-knockout (KO) and -wildtype (WT) mice underwent a four-week-mild CS paradigm or non-stress control (C) condition. After C or CS, behaviours, hippocampal microstructures (via MRI-based diffusion tensor imaging) and brain gene expression profiles (via mRNA-seq transcriptomics) were investigated. Analyses focused on effects of genotype (KO vs. WT) or condition (C vs. CS) separately in both sexes. Our results revealed significant effects particularly in females. Female KOs displayed increased locomotion and reduced depression-like behaviour after CS (KO vs. WT, C vs. CS: p all  < 0.05). Hippocampal fibres were reduced in female KOs after C (KO vs. WT: p all  < 0.05) but in female WTs after CS (C vs. CS: p all  < 0.05). Furthermore, female KOs showed increased cortistatin expression after CS (C vs. CS: mRNAseq and qPCR p all  < 0.05). In sum, Zdhhc7-deficiency reduced depression-like behaviours, prevented hippocampal fibre reduction and upregulated cortistatin after CS. It seemed to be related to a sex-specific stress response and may reveal genetic factors of CS-resilience in female mice.